Depression, hope, risk-taking participation and suicidal behavior among Malaysian adolescents - Choon, Min Wai (2016)
The present study examined the relationship between depressive symptoms, hope, risk taking participation and suicidal behavior. There were a total of 1314 adolescents aged between 13 to 17 years (M=15.27, SD=1.02) participated in the study. All the respondents were recruited by utilizing multistage cluster sampling. Two theories were integrated to highlight the argument of the present study on suicidal behavior (Bandura, 1999; Joiner, 2005). Based on Bandura’s social cognitive theory, hope was conceptualized from self-efficacy as a protective factor in explaining suicidal behavior. Meanwhile, the interpersonal-psychological theory of suicide (Joiner, 2005) emphasized on both constructs (desire to die and ability to die) which have been conceptualized into depressive symptoms and risk taking participation in explaining suicidal behavior among adolescents. Suicidal Behavior Questionnaire-Revised (Osman et al., 1999) was used to assess suicidal behavior. Meanwhile, Adolescent Exploratory and Risk Behavior Rating Scale developed by Skaar (2009) assesses adolescents’ risk taking participations. Depressive symptoms were assessed by adapting Centre for Epidemiologic Studies Depression Scale (Radloff, 1977) while Children’s Hope Scale (Snyder et al., 1997) was used to measure hope. The acquired data was analyzed using descriptive statistics, Pearson correlation, and regression analyses respectively. Results indicated a 20.7% of adolescents (n=272) engaged in suicidal behavior. The result also indicated that all studied variables were significantly correlated except for exploratory risk and depressive symptoms. Interestingly, health risk behaviors were found to partially mediate the relationship between depressive symptoms and suicidal behavior. In contrast, exploratory risk behaviors however was found to partially mediated the relationship between hope and suicidal behavior. The results obtained from the present study substantiated the previously mentioned theories of Bandura (1999) and Joiner (2005) by emphasizing the partial mediation of risk taking participations in the relationship between depressive symptoms, hope, and suicidal behavior. Future studies could further explore these findings in an in-depth manner to achieve clearer understanding on the intervention of suicidal behavior through risk taking participations.